Numerical analysis on failure pressure of pipelines with multi-corroded region - Ng, Yew Keong (2013)
The underground gas pipeline is vulnerable which can explode any time. The percentage of the pipeline fails due to the pressure may cause fatal destruction. Hence, the predictions of pipeline burst pressure in the early stage are very important in order to provide assessment for future inspection, repair and replacement activities. This thesis is to study the effect of multiple corrosion defects on failure pressure for API X42 steel and validate the results with available design codes. The project implicates analysis by using MSC Patran 2008 r1 software as a pre-processor and MSC Marc 2008 r1 software as a solver. Half of the pipe was simulated by fully applying symmetrical condition. The pipe is modeled in 3-D with outer diameter 381 mm, wall thickness of 17.5 mm and different defect parameter. In this analysis, SMCS and von Mises stress used to predict the failure pressure. The result shows that the failure pressure increases when the distance between defect increases but decreases when the defect length increases. SMCS always shows a higher value compared to von Mises. The design codes applied only when the distance between defect is small enough that multiple defects acts as a single defect. Meanwhile, value of FEA is the highest among all the design codes.